Effect of heat treatment on interfacial bonding and strengthening efficiency of graphene in GNP/Al composites. (June 2019) - Li, Jianchao; Zhang, Xuexi; Geng, Lin
Abstract: Interfacial bonding state between graphene nano-platelets (GNP) and aluminum strongly influences the strengthening efficiency of GNP/Al composites. Here, 2.0 wt% GNP/Al composites were annealed at various temperatures to explore the effects of heat treatment on microstructure, mechanical properties and strengthening behavior of graphene. Interfacial reaction between GNP and Al occurred in composite annealed at 650 °C, but was absent in 600 °C annealed composite. The composite fracture mode changed from GNP pull-out to GNP fracture with increasing annealing temperatures, implying improved interfacial bonding strength. The ultimate tensile strength (UTS) predicted by the shear-lag model agreed well with experimental data, suggesting that load transfer played a significant role in the composite strength. However, the thermal mismatch stress induced by GNPs was much smaller than that via theoretical calculations. Finally, with rising annealing temperature, the strengthening efficiency of graphene was greatly enhanced owing to the improved interfacial bonding between GNP and Al matrix.